Availability and Utilization of World Health Organization Recommended Priority Life-Saving Medicines for Under Five-Year-Old Children in Gondar Town, Ethiopia: A Cross-Sectional Study - Woldeyohanins AE; Kasahun AE; Demeke CA; Kifle ZD (Dove Medical Press, 2021)
Alem Endeshaw Woldeyohanins,1 Asmamaw Emagn Kasahun,1 Chilot Abiyu Demeke,1 Zemene Demelash Kifle2 1Department of Pharmaceutics and Social Pharmacy, School of Pharmacy Gondar, University of Gondar-College of Medicine and Health Sciences, Gondar, Ethiopia; 2Department of Pharmacology, School of Pharmacy Gondar, University of Gondar-College of Medicine and Health Sciences, Gondar, EthiopiaCorrespondence: Alem Endeshaw WoldeyohaninsDepartment of Pharmaceutics and Social Pharmacy, School of Pharmacy Gondar, University of Gondar-College of Medicine and Health Sciences, P.O. Box 196, Gondar, EthiopiaTel +251 920292874Fax +251-58-1141240Email aleend2008@gmail.com; Alem.Endashaw@uog.edu.etBackground: Globally, more than eight million under-five children die every year because of diseases that could be treated or prevented with drug therapy. Thus, this study aimed to evaluate the utilization and availability of the World Health Organization (WHO) suggested priority life-saving medicines for under-five-year-old children in Gondar town.Methods: Institutional-based cross-sectional survey was conducted from March 2020 to May 2020 in public health centers of Gondar town. Data entry and validation were performed in EpiData 3.1 and exported to SPSS version 20 for descriptive analysis like frequency, percentage, mean, standard deviation, and median.Results: The availability of zinc phosphate and oral rehydration salt for the diarrheal cases was 57.14% and 85.71%, respectively. The availabilities of amoxicillin dispersible tablet and gentamicin injection for the treatments of pneumonia cases were 71.43% and 42.85%, respectively, and the availability of paracetamol tablet was high (85.71%). The availabilities of artemether/lumefantrine tablet and artesunate rectal were ranged between fairly high (57.1%) to very low (28.5%), respectively, and the availabilities of zidovudine/lamivudine/nevirapine-based antiretroviral regimen was 100%, a utilization for this regimen was high (96.29%). Two (3.70%) of the surveyed cases were utilized lopinavir/ritonavir-based regimen. The utilization of priority medicines was low for pain management and pneumonia which was 18.5% and 48.18%, respectively.Conclusion: The study concluded that medicine was not consistently available throughout public health centers in Gondar town. Thus, this finding suggests the integration of WHO-recommended life-saving priority medicines into the essential drug management systems and health unit logistics to raise their utilization and availability.Keywords: availability, utilization, priority medicines, Gondar, Ethiopia